Pembelajaran IPS Berbasis Literasi (Gerakan Literasi Sekolah Tahap Pembelajaran) pada Kelas VIII di SMP N 2 Banyubiru - Anwar, Saiful; Nisa, Aisyah Nur Sayidatun (Universitas Negeri Semarang, 2020)
The implementation of the 2013 curriculum in learning one emphasizes the importance of literacy skills with the existence of the school literacy movement. The literacy movement at SMPN 2 Banyubiru has been running but has not been implemented optimally, especially at the learning stage and is still at the development stage. The research method used is a qualitative method, because it is to find out the activities and implementation of literacy in learning Social Sciences. The results showed: 1) Social literacy-based learning model used is a problem-based learning model and its implementation in the classroom requires the role of teachers and students, 2) There are obstacles faced by teachers in the planning, implementation and evaluation stages, 3) Learning outcomes students have differences after attending literacy-based social studies learning, whether those grades have increased or still remain the same.